Emotional Intelegence Sebagai Salah Satu Faktor Penunjang Prestasi Kerja - Jacinta Winarno (Jurnal Manajemen Maranatha, 2008)
People who have an average academic level but have a high level of Emotional Quotient (EQ) will be more successful in working compared with those who have a high academic record and a high Intelligence Quotient (IQ) and who is a graduate from a favourite university but who have a low Emotional Quotient (EQ). Therefore one tends to be more successful because of one’s high Emotional Inteligence (EI) rather than one’s intellectual intelligence. Emotional Intelegence is often measured as Emotional Quotient (EQ). Several experts state that IQ gets you hired and EQ gets you promoted. The basic of emotional capability is self awareness, that is knowing about one’s own capability and limit including a deep understanding of factors and situation which can excite emotion in oneself.